Magnetic composite particle material, preparation method thereof and application thereof in repairing infectious bone defects
Patent Information
- Application Number
- CN202611122415.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-07-28
AI Technical Summary
然而,现有技术中上述功能仍需单独执行,尚未实现上述功能的集中化和一体化
[0020]本发明的有益效果如下:本发明提供的多功能磁性复合颗粒材料具有良好的磁响应性和稳定的离子释放行为,有利于其在体内发挥作用。该磁性复合颗粒材料不仅具有良好的生物相容性,还具有良好的生物活性,可促进人骨髓间充质干细胞的黏附、增殖与迁移;通过结合静磁场共同作用,这些促进效应得到进一步增强,能确保材料能够在体内安全存在,为后续组织修复提供基础。细胞水平上的体外促成骨性能测试结果显示,该磁性复合颗粒材料,尤其是与静磁场的共同作用下,可在成骨诱导的早期和中晚期阶段持续促进人骨髓间充质干细胞的成骨分化,并推动矿化成熟,具有显著的促成骨优势。体外抗菌性能测试结果表明,该磁性复合颗粒材料可有效抑制细菌(大肠杆菌、金黄色葡萄球菌、粪肠球菌)的生长,在静磁场的联合作用下,抗菌效果还表现出一定的增强趋势。植入大鼠股骨感染性骨缺损区域后,该材料能有效抑制细菌生长、促进新骨形成,并具有良好的体内生物安全性,与静磁场的联合作用可进一步增强材料的体内抗感染效果及促进骨再生能力,表明其具有良好的体内活性,展现了出色的临床应用潜力。该磁性复合颗粒材料的制备方法简便高效,不需要复杂的制备设施及处理条件,生产成本低,具有较高的商业价值。
Smart Images

Figure CN122643502B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomedical repair materials technology, specifically to a magnetic composite particle material, its preparation method, and its application in the repair of infected bone defects. Background Technology
[0002] Infectious bone defects, caused by infections associated with osteomyelitis, trauma, or fractures, are characterized by the coexistence of bone tissue defects and infection. Clinical treatment often presents the significant challenge of simultaneously controlling infection and promoting bone repair. Current treatments for infectious bone defects primarily include debridement surgery, antibiotic therapy, and autologous / allogeneic bone grafting or scaffold implantation. However, these methods suffer from limitations such as donor availability, immune rejection, antibiotic overuse, and the increasing prevalence of drug-resistant strains. Furthermore, insufficient blood supply to the infection site makes it difficult to maintain effective drug concentrations, and prolonged inflammation deteriorates the local microenvironment, exacerbating the imbalance between bone formation and resorption. Conversely, the high local concentrations required for potent antibacterial agents may conflict with the mild microenvironment needed for tissue regeneration. These issues severely restrict the treatment outcomes of infectious bone defects, impacting patients' quality of life and imposing a heavy economic burden on society. Therefore, developing a multifunctional integrated treatment strategy that combines targeted enrichment, antibacterial action, and bone-promoting function is crucial.
[0003] In recent years, biomedical magnetic materials have become an ideal platform for constructing multifunctional therapeutic systems due to their unique magnetic responsiveness, good biocompatibility, and ease of surface modification. Magnetic particles, guided by an external magnetic field, can achieve targeted enrichment of lesions, making them particularly suitable for complex anatomical sites with deep tissues and poor blood supply. Furthermore, their surfaces are easily modified, allowing for the integration of different functional modules. Simultaneously, the external magnetic field not only guides the magnetic particles but also enhances bactericidal effects by increasing interfacial contact and reactive oxygen species generation, and influences stem cell osteogenic behavior by regulating cell adhesion, skeletal remodeling, and related signaling pathways. However, in existing technologies, these functions still need to be performed individually, and their centralization and integration have not yet been achieved. Therefore, how to construct a multifunctional bone defect repair material system integrating antibacterial, osteogenic, and magnetic response regulation capabilities has become a pressing technical problem that needs to be solved by those skilled in the art. Summary of the Invention
[0004] To address the aforementioned technical problems, this invention provides a magnetic composite particle material, its preparation method, and its application in the repair of infected bone defects.
[0005] This invention provides a magnetic composite particle material, composed of magnetic composite particles, wherein the magnetic composite particles comprise the following parts from the inside out: The magnetic core comprises magnetite particles modified with polyacrylic acid, wherein magnesium ions are adsorbed on the surface of the magnetite particles. An intermediate transition layer comprising polydopamine wrapped around the surface of the magnetic core, wherein copper oxide is externally loaded onto the polydopamine. An outer wrapping layer, which is composed of chitosan, is wrapped around the outside of the intermediate transition layer.
[0006] Furthermore, the particle size of the magnetic composite particles is 250~550nm, such as 260~540nm, 270~530nm, 280~520nm, 290~510nm, 300~500nm, 310~490nm, 320~480nm, 330~470nm, 340~460nm, preferably 350~450nm.
[0007] Another aspect of the present invention provides a method for preparing the above-mentioned magnetic composite particle material, comprising the following steps: Preparation of polyacrylic acid modified magnetite magnetic particles: Soluble iron salts were dissolved in an organic solvent, polyacrylic acid was added, the mixture was transferred to a high-pressure reactor and placed in an electric heating drying oven for high-temperature reaction. After the reaction was completed, the precipitate in the high-pressure reactor was separated by a magnet, washed and then vacuum dried to obtain polyacrylic acid modified magnetite magnetic particles. Preparation of magnetic composite particles: The magnetic particles are dispersed in an aqueous solution of magnesium chloride, and subjected to ultrasonic treatment and mechanical stirring to adsorb magnesium ions on the surface of the magnetic particles; dopamine is added and mixed, then copper oxide is added and mixed to form the intermediate transition layer; chitosan solution is added to the reaction system and reacted in the dark to form the outer coating layer; the reaction product is then washed and vacuum dried to obtain the magnetic composite particles.
[0008] Furthermore, the specific method for preparing the polyacrylic acid-modified iron oxide magnetic particles is as follows: Polyacrylic acid-modified magnetite particles were synthesized using a one-pot solvothermal method, with a dosage of 2-5g per 120ml of solvent (e.g., 2g, 2.25g, 2.5g, 2.75g, 3g, 3.25g, 3.5g, 3.75g, 3.9g, 3.95g, 4g, 4.05g, 4.1g, 4.25g, 4.5g, 4.75g, or 5g, or any two consecutive values thereof). Weigh out the sample containing ferric chloride hexahydrate and 10.8 g of sodium acetate powder (any value between these values), disperse it in an ethylene glycol solution, and then add the following amount per 120 mL of solvent: 0.025–0.5 g (e.g., 0.025 g, 0.05 g, 0.075 g, 0.1 g, 0.125 g, 0.15 g, 0.175 g, 0.2 g, 0.225 g, 0.25 g, 0.275 g, 0.3 g). Add polyacrylic acid at doses of 0.325g, 0.35g, 0.375g, 0.4g, 0.425g, 0.45g, 0.475g, or 5g (or any value between any two adjacent values) and stir overnight to completely dissolve the powder. Transfer the mixture to a stainless steel high-pressure reactor with a Teflon liner and place it in a 200°C electric heating drying oven for 8-12 hours (e.g., 8h, 8.5h, 9h, 9.5h, 10h, 10.5h, 11h, 11.5h, or 12h (or any value between any two adjacent values) after the reaction is complete. After the reaction is complete and the reactor is cooled, separate the precipitate in the liner using a magnet and wash several times alternately with deionized water and anhydrous ethanol. Dry the washed precipitate under vacuum at room temperature to obtain the polyacrylic acid-modified iron oxide magnetic particles.
[0009] Furthermore, the specific method for preparing the magnetic composite particles is as follows: The polyacrylic acid-modified magnetite particles were dispersed in a magnesium chloride aqueous solution at a concentration of 0.1–0.4 mol / L (e.g., 0.1 mol / L, 0.125 mol / L, 0.15 mol / L, 0.175 mol / L, 0.2 mol / L, 0.225 mol / L, 0.25 mol / L, 0.275 mol / L, 0.3 mol / L, 0.325 mol / L, 0.35 mol / L, 0.375 mol / L, or 0.4 mol / L, or any value between any two adjacent values). After ultrasonic treatment for 0.25–1 h, the solution was mechanically stirred for 2–8 h, followed by washing of the precipitate. The precipitate was then dispersed in a 10 mM solution. In Tris-HCl buffer, after sonication for 0.25–1 h, dopamine is added at a rate of 1–4 mg / mL, and the mixture is mechanically stirred for 0.5–2 h. Subsequently, 5–20 mg (e.g., 5 mg, 6 mg, 7 mg, 8 mg, 9 mg, 10 mg, 11 mg, 12 mg, 13 mg, 14 mg, 15 mg, 16 mg, 17 mg, 18 mg, 19 mg, or 20 mg, or any value between any two adjacent values) of copper oxide is added at a mass of 1 / 10–2 / 5 of the mass of the polyacrylic acid-modified iron oxide. After sonication for 0.25–1 h, stirring is continued for 1–4 h to allow dopamine to self-polymerize and form polydopamine. After the reaction, the precipitate is washed and then stored in a cool, dry place. The intermediate product was obtained by vacuum drying at room temperature. A chitosan solution of 0.5-2 w / v% (e.g., 0.5 w / v%, 0.6 w / v%, 0.7 w / v%, 0.8 w / v%, 0.9 w / v%, 1 w / v%, 1.1 w / v%, 1.2 w / v%, 1.3 w / v%, 1.4 w / v%, 1.5 w / v%, 1.6 w / v%, 1.7 w / v%, 1.8 w / v%, 1.9 w / v%, or 2 w / v, or any value between any two adjacent values) was prepared with 1% glacial acetic acid solution. The intermediate product was added, and after uniform dispersion, a crosslinking agent was added. The reaction was carried out in the dark for 1-4 hours, and the product was washed and vacuum dried at room temperature to obtain the magnetic composite particles.
[0010] Furthermore, the chitosan solution is prepared as follows: Chitosan powder was dissolved in a pre-prepared 1% glacial acetic acid solution, heated to 50°C, and stirred for 0.5 to 1 hour until the solution was clear and transparent. The pH of the solution was adjusted to 5 to 6 with sodium hydroxide solution, and then filtered to obtain the chitosan solution.
[0011] A third aspect of the present invention provides the use of the above-mentioned magnetic composite particle material in the preparation of medicaments and / or medical devices for treating infectious bone defects.
[0012] A fourth aspect of the present invention provides an formulation for treating infected bone defects, comprising the following components: The aforementioned magnetic composite particle material; and GelMA hydrogel solution.
[0013] Further, in the formulation, the content of the magnetic composite particle material is 40~80 μg / mL (e.g., 40 μg / mL, 45 μg / mL, 50 μg / mL, 55 μg / mL, 57.5 μg / mL, 60 μg / mL, 62.5 μg / mL, 65 μg / mL, 70 μg / mL, 75 μg / mL or 80 mol / L, or any value between any two adjacent values), and the concentration of the GelMA hydrogel solution is 5~30 w / v% (e.g., 5 w / v). %, 6w / v%, 7w / v%, 8w / v%, 9w / v%, 10w / v%, 11w / v%, 12w / v%, 13w / v%, 14w / v%, 15w / v%, 17.5w / v%, 20w / v%, 22.5w / v%, 25w / v%, 27.5w / v%, or 30w / v, or any value between any two adjacent values).
[0014] In a preferred embodiment, the content of the magnetic composite particle material in the formulation is 60 μg / mL.
[0015] In a preferred embodiment, the concentration of the GelMA hydrogel solution in the formulation is 10 w / v.
[0016] In a preferred embodiment, the preparation is an injection.
[0017] A third aspect of the present invention provides a kit for treating infected bone defects, comprising the following parts: The above-mentioned preparations; and Permanent magnets used to generate static magnetic fields.
[0018] In a preferred embodiment, the magnetic field strength of the static magnetic field is 10~100mT (e.g., 10mT, 15mT, 20mT, 25mT, 30mT, 35mT, 40mT, 45mT, 50mT, 55mT, 60 mT, 65 mT, 70mT, 75 mT, 80 mT, 85 mT, 90 mT, 95 mT or 100 mT, or any value between any two adjacent values).
[0019] In a preferred embodiment, the permanent magnet is a neodymium iron boron permanent magnet.
[0020] The beneficial effects of this invention are as follows: The multifunctional magnetic composite particle material provided by this invention has good magnetic responsiveness and stable ion release behavior, which is beneficial for its function in vivo. This magnetic composite particle material not only has good biocompatibility but also good biological activity, promoting the adhesion, proliferation, and migration of human bone marrow mesenchymal stem cells. These promoting effects are further enhanced by the combined action of a static magnetic field, ensuring the material's safe existence in vivo and providing a foundation for subsequent tissue repair. In vitro osteogenic performance tests at the cellular level show that this magnetic composite particle material, especially under the combined action of a static magnetic field, can continuously promote osteogenic differentiation of human bone marrow mesenchymal stem cells in the early and late stages of osteogenic induction and promote mineralization maturation, exhibiting a significant osteogenic advantage. In vitro antibacterial performance tests show that this magnetic composite particle material can effectively inhibit the growth of bacteria (Escherichia coli, Staphylococcus aureus, Enterococcus faecalis), and the antibacterial effect shows a certain enhancing trend under the combined action of a static magnetic field. After implantation into infected bone defect areas of the rat femur, this material effectively inhibited bacterial growth, promoted new bone formation, and exhibited good in vivo biocompatibility. The combined effect with a static magnetic field further enhanced the material's in vivo anti-infective efficacy and bone regeneration capacity, demonstrating its excellent in vivo activity and promising clinical application potential. The preparation method of this magnetic composite particle material is simple and efficient, requiring no complex preparation facilities or processing conditions, resulting in low production costs and high commercial value. Attached Figure Description
[0021] One or more embodiments are illustrated by way of example with reference to the accompanying drawings, and these illustrative examples are not intended to limit the embodiments. The term "illustrative" as used herein means "serving as an example, embodiment, or illustration." Any embodiment illustrated herein as "illustrative" is not necessarily to be construed as superior to or better than other embodiments.
[0022] Figure 1 This is a schematic diagram of the structure of the magnetic composite particles prepared according to the present invention.
[0023] Figure 2 This is a schematic diagram illustrating the preparation methods of the magnetic particles Fe3O4, P-Fe3O4 in the examples and the magnetic particles F-Fe3O4 in the comparative example.
[0024] Figure 3The images shown are SEM images of the magnetic particles in Experimental Example 1, where: A: SEM image and DLS particle size distribution of Fe3O4 prepared in Comparative Example 1; B: SEM image and DLS particle size distribution of P-Fe3O4 prepared in Example 1; C-E: TEM images of Fe3O4 prepared in Comparative Example 1 at different magnification ratios; F-H: TEM images of P-Fe3O4 prepared in Example 1 at different magnification ratios; I: SEM image and DLS particle size distribution of F-Fe3O4 prepared in Example 1; J: TEM image of F-Fe3O4 prepared in Example 1; K: SEM image of P-Fe3O4 prepared in Example 2; L: SEM image of F-Fe3O4 prepared in Example 2.
[0025] Figure 4 The following are the characterization results of the basic physicochemical properties of the magnetic particles in Experimental Example 1, including: A: Nitrogen isothermal adsorption-desorption curves of Fe3O4 prepared in Comparative Example 1 and P-Fe3O4 prepared in Example 1; B: Pore size distribution of Fe3O4 prepared in Comparative Example 1 and P-Fe3O4 prepared in Example 1; C: Zeta potential of Fe3O4 prepared in Comparative Example 1 and P-Fe3O4 and F-Fe3O4 prepared in Example 1; D: EDS elemental distribution map (molybdenum grid) of F-Fe3O4 prepared in Example 1; E: Individual elemental distribution map of carbon, nitrogen, oxygen, magnesium, iron and copper in F-Fe3O4 prepared in Example 1.
[0026] Figure 5 The following are the chemical structure and magnetic properties characterization results of the magnetic particles in Experiment Example 2, including: A: XRD patterns of P-Fe3O4 and F-Fe3O4; B: hysteresis curves of P-Fe3O4 and F-Fe3O4; C: Thermogravimetric analysis results of P-Fe3O4 and F-Fe3O4; D: FTIR spectra of different magnetic particles; E: XPS full spectrum of P-Fe3O4 and F-Fe3O4; F: Ion release trend of F-Fe3O4.
[0027] Figure 6 The results of the in vitro biocompatibility experiment of the magnetic particles in Experiment Example 3 are as follows: A: Live / dead staining images of human bone marrow mesenchymal stem cells in different magnetic particle groups; B: Cytoskeleton staining images; C: Cell proliferation detected by CCK-8 assay; D: Cell scratch assay images; E: Quantitative analysis of scratch assay results. In C and E, * p <0.05,** p <0.01, *** p <0.001, ns indicates no significant difference. p ≥0.05.
[0028] Figure 7The results of the in vitro osteogenic properties experiment of the magnetic particles in Experiment Example 4 are shown, including: A: ALP staining images of human bone marrow mesenchymal stem cells in different magnetic particle groups; B: Staining images of mineralized nodules; C: Quantitative analysis of ALP activity; D: Quantitative analysis of mineralized nodules; E: ALP Gene expression status; F: RUNX2 Gene expression status; G: BGLAP Gene expression status; H: SPP1 Gene expression status. In C~H, * p <0.05,** p <0.01, *** p <0.001, ns indicates no significant difference. p ≥0.05.
[0029] Figure 8 The results of the in vitro antibacterial performance test of the magnetic particles in Experiment Example 5 are shown below: A: Plate images of Escherichia coli, Staphylococcus aureus, and Enterococcus faecalis in different magnetic particle groups; B: Activity analysis of Escherichia coli; C: Activity analysis of Staphylococcus aureus; D: Activity analysis of Enterococcus faecalis; E: SEM morphology images of the three bacteria. In B~D, * p <0.05,** p <0.01, *** p <0.001, ns indicates no significant difference. p ≥0.05.
[0030] Figure 9 The results of the in vivo antibacterial performance experiment of the magnetic particles in Experiment Example 6 are shown, including: A: bacterial plate images of different magnetic particle groups one week after surgery; B: bacterial survival rate analysis; C: H&E staining images of infected soft tissue sections; D: Giemsa staining images of infected soft tissue sections. In B, * p <0.05,** p <0.01, *** p <0.001, ns indicates no significant difference. p ≥0.05.
[0031] Figure 10 The results of the in vivo osteogenic properties experiment of the magnetic particles in Example 6 are as follows: A: Three-dimensional reconstructed images of bone defect areas in different magnetic particle groups at 4 weeks post-operation; B: Three-dimensional reconstructed images of bone defect areas in different magnetic particle groups at 8 weeks post-operation; C-F: Quantitative analysis of infected bone defect areas at 4 and 8 weeks post-operation (bone volume fraction, number of trabeculae, trabecular thickness, and trabecular distance). In C-F, * p <0.05,** p <0.01, *** p<0.001, ns indicates no significant difference. p ≥0.05.
[0032] Figure 11 Images of stained bone tissue sections from the in vivo osteogenic performance experiment of the magnetic particles in Example 6 are shown, where: A: H&E stained bone tissue section; B: Masson stained bone tissue section; C: Osteocalcin stained bone tissue section.
[0033] Figure 12 The results of the in vivo biosafety experiment of the magnetic particles in Example 6 are as follows: A: H&E staining images of rat major organ sections in different magnetic particle groups 1 week after surgery; B: H&E staining images of rat major organ sections in different magnetic particle groups 4 weeks after surgery; C: H&E staining images of rat major organ sections in different magnetic particle groups 8 weeks after surgery. Detailed Implementation
[0034] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Unless otherwise expressly stated, throughout the specification and claims, the term "comprising" or its variations such as "including" or "comprising of," etc., will be understood to include the stated elements or components, and does not exclude other elements or other components.
[0035] Furthermore, to better illustrate the present invention, numerous specific details are set forth in the following detailed embodiments. Those skilled in the art will understand that the present invention can still be practiced even without certain specific details. In some embodiments, materials, elements, methods, and means well known to those skilled in the art are not described in detail in order to highlight the spirit of the invention.
[0036] The magnetic composite particle material F-Fe3O4 (P-Fe3O4-Mg²) provided by this invention + The multi-layer structure of @PDA / CuO@CS) is as follows Figure 1 As shown, P-Fe3O4 modified with polyacrylic acid (PAA) serves as the magnetic core material, providing a foundation for achieving external field response and precise local enrichment. By adding polyacrylic acid to the solvothermal reaction system, not only is the specific surface area of the iron oxide particles increased, but their surface charge is also altered, improving particle dispersion and providing favorable conditions for subsequent modification. Based on the negatively charged surface of P-Fe3O4, magnesium ionsAnionic polyacrylic acid can be used to provide anionic polyacrylic acid (PA) COO Electrostatic adsorption occurs at the sites of the carboxylic acid polysaccharide (MAP), and ionic interactions are generated. Furthermore, magnesium ions exhibit a "bridging effect," bridging anionic groups and thus strengthening the intermolecular interactions of MAPs. This suggests that magnesium ions in this system may possess certain multifunctional roles.
[0037] Polydopamine (PDA) is a polymer material inspired by the adhesive proteins of marine mussels. It can adhere to the surfaces of various inorganic and organic materials to form thin layers, and is therefore often used as an intermediate carrier to provide a platform for secondary functionalization in multilayer structures. In the F-Fe3O4 system of this invention, the PDA layer is located between the magnetic core and the outer functional components, providing anchoring sites for the loading of copper oxide and the construction of the chitosan shell. Furthermore, ICP results showed that copper was released rapidly in the early stages, followed by limited release and a plateauing trend. This release pattern may be due to the rapid dissolution of copper initially bound to the material surface or weakly bound, while later, the functional groups in PDA and chitosan chelate the metal ions. In contrast, magnesium modified in ionic form showed a more stable and gradually increasing release trend. Iron release was relatively low and slow, possibly due to the good stability of iron(III) oxide itself, and its location in the inner layer, which restricts the migration of iron ions.
[0038] The F-Fe3O4 of this invention exhibits excellent biocompatibility and promotes cell adhesion, proliferation, and migration not only because its core is made of iron(III) oxide, but also because the subsequent modifying materials selected are magnesium ions, polydopamine, and chitosan. Specifically, magnesium exists as a bioactive module in the F-Fe3O4 system, and the continuous release of magnesium ions demonstrates various biological activities, including improving cell adhesion, stimulating differentiation, and promoting the neural, vascular, and osteogenic differentiation of bone marrow mesenchymal stem cells, thereby supporting the formation of neurovascularized bone tissue. Materials modified with polydopamine are commonly used for tissue repair; they have good hydrophilicity, enhance cell adhesion, and create a microenvironment more conducive to tissue regeneration.
[0039] Chitosan (CS) is a natural aminopolysaccharide with good biocompatibility, plasticity, and bioactivity. Animal experiments suggest that the copper-based component in this system exhibits a rapid-then-slow release behavior, maintaining a low release level in vivo after infection control, thus reducing associated toxicity risks and preventing negative impacts on biosafety. This also suggests that the copper-based component in F-Fe3O4 has the potential for sustained contributions, ranging from antibacterial activity to participation in angiogenesis, osteogenic processes, and microenvironment regulation, in infectious bone defects, thereby promoting tissue regeneration and repair.
[0040] For the treatment of infected bone defects, the antibacterial properties of biomaterials are crucial. In the F-Fe3O4 system, copper oxide and chitosan, as outer components, play a dominant role in antibacterial activity. Copper ions exhibit concentration-dependent activity, meaning they are effective at high concentrations but may possess potential cytotoxicity at excessively high concentrations. Therefore, controlling the immobilization and release of copper ions is essential. In the F-Fe3O4 system, the biphasic release pattern of copper (i.e., early burst release followed by slow, sustained release) indicates that F-Fe3O4 can provide a strong ion signal in the early stages to promote antibacterial activity while reducing the risk of subsequent cytotoxicity. In F-Fe3O4, chitosan, located on the outermost layer of the particles, not only maintains the biocompatibility of the material but also further enhances its antibacterial effect. Chitosan and its derivatives can interact with bacterial cell membranes through electrostatic interactions. Their positively charged amino groups bind to negatively charged components on the bacterial surface (such as lipopolysaccharides), disrupting the integrity and permeability of the cell membrane, leading to cytoplasmic leakage and bacterial death. Furthermore, the copper-based components in the F-Fe3O4 system are loaded with copper oxide rather than copper salts, which avoids the weakening of the material's antibacterial properties caused by the chelation effect of chitosan. Therefore, chitosan and copper oxide in the F-Fe3O4 system, together as an outer antibacterial component with broad-spectrum antibacterial function, can synergistically exert a more effective and concentrated antibacterial effect in the early stage of infection.
[0041] The methacrylamide gelatin (GelMA) and its initiator lithium phenyl (2,4,6-trimethylbenzoyl)phosphate used in the following examples were purchased from EFL-Tech (Suzhou, China). The hydrogel solution was prepared and used in accordance with the manufacturer's instructions.
[0042] Unless otherwise specified, the other reagents and instruments used in the following examples are commercially available reagents and instruments commonly used in the field and can be purchased or obtained through conventional channels.
[0043] In the following examples, the crosslinking agent used is 5% glutaraldehyde, in a volume of 5-100 μL. In other embodiments, glutaraldehyde can be replaced with other commonly used crosslinking agents, such as genipin, sodium tripolyphosphate, etc.
[0044] Example 1 This embodiment provides a magnetic composite particle material, which, through methods such as... Figure 2 It was prepared by the method shown in the figure.
[0045] S1: Preparation of magnetic core particles P-Fe3O4: Polyacrylic acid-modified iron(III) oxide particles (P-Fe3O4) were synthesized using a one-pot solvothermal method. 4.05 g of FeCl3·6H2O and 10.8 g of sodium acetate (NaAc) powder were weighed and dispersed in 120 mL of ethylene glycol (EG) solution. Then, 0.125 g of polyacrylic acid was added and stirred overnight until the powder was completely dissolved. The mixture was transferred to a stainless steel high-pressure reactor with a Teflon liner and placed in a 200°C electric heating drying oven for 12 h. After the reaction was complete, the reactor was cooled, and the precipitate in the liner was separated using a magnet. The precipitate was washed several times alternately with deionized water and anhydrous ethanol. The washed precipitate was then vacuum dried at room temperature to obtain P-Fe3O4 particles.
[0046] S2: Preparation of magnetic composite particles F-Fe3O4: 50 mg of P-Fe3O4 was dispersed in 50 mL of 0.2 mol / L magnesium chloride aqueous solution. After sonication for 0.5 h, the solution was mechanically stirred for 4 h, followed by washing of the precipitate. The product was then dispersed in 10 mM Tris-HCl buffer and sonicated for 0.5 h. Dopamine was added at a concentration of 2 mg / mL, and the solution was mechanically stirred for 1 h. Subsequently, 10 mg of copper oxide was added, and the solution was sonicated for 0.5 h, followed by stirring for another 2 h to allow dopamine to self-polymerize and form polydopamine, yielding the intermediate product P-Fe3O4-Mg². + @PDA / CuO. A 1.0 w / v chitosan solution was prepared using 1% glacial acetic acid solution. The solution was heated to 50°C and stirred for 1 hour until clear and transparent. The pH of the chitosan solution was adjusted to 5.5 with sodium hydroxide solution and then filtered. 50 mL of the filtered chitosan solution was added to the above intermediate product. After uniform dispersion, 50 μL of 5% glutaraldehyde was added. The reaction was carried out in the dark for 2 hours. The product was then washed and vacuum dried at room temperature to obtain F-Fe3O4 particles (P-Fe3O4-Mg²). + @PDA / CuO@CS).
[0047] Example 2 This embodiment provides a magnetic composite particle material, which, through methods such as... Figure 2 It was prepared by the method shown in the figure.
[0048] S1: Preparation of magnetic core particles P-Fe3O4: P-Fe3O4 particles modified with polyacrylic acid were synthesized using a one-pot solvothermal method. 4 g of FeCl3·6H2O and 10.8 g of sodium acetate powder were weighed and dispersed in 120 mL of ethylene glycol solution. Then, 0.375 g of polyacrylic acid was added and stirred overnight until the powder was completely dissolved. The mixture was transferred to a stainless steel high-pressure reactor with a Teflon liner and placed in a 200°C electric heating drying oven for 10 h. After the reaction was complete, the reactor was cooled, and the precipitate in the liner was separated using a magnet. The precipitate was washed several times alternately with deionized water and anhydrous ethanol. The washed precipitate was then vacuum dried at room temperature to obtain P-Fe3O4 particles.
[0049] S2: Preparation of magnetic composite particles F-Fe3O4: 50 mg of P-Fe3O4 was dispersed in 50 mL of 0.1 mol / L magnesium chloride aqueous solution. After sonication for 0.25 h, the mixture was mechanically stirred for 2 h, followed by washing of the precipitate. The product was dispersed in 10 mM Tris-HCl buffer and sonicated for 1 h. Dopamine was then added at a concentration of 1 mg / mL, and the mixture was mechanically stirred for 1 h. Subsequently, 5 mg of copper oxide was added, and the mixture was sonicated for 0.25 h followed by stirring for another 2 h to allow dopamine to self-polymerize and form polydopamine, yielding an intermediate product with polydopamine encapsulation. A 1.0 w / v% chitosan solution was prepared using 1% glacial acetic acid solution, heated to 50 °C, and stirred for 1 h until the solution was clear and transparent. The pH of the chitosan solution was adjusted to 6 with sodium hydroxide solution and filtered. 50 mL of the filtered chitosan solution was added to the above intermediate product. After uniform dispersion, 50 μL of 5% glutaraldehyde was added, and the mixture was reacted in the dark for 3 h. The product was then washed and vacuum dried at room temperature to obtain F-Fe3O4 particles.
[0050] Comparative Example 1 A magnetic particle material, through such Figure 2 It was prepared by the method shown in the figure.
[0051] Magnetic Fe3O4 particles were synthesized using a one-pot solvothermal method. 4 g of FeCl3·6H2O and 10.8 g of sodium acetate powder were weighed and dispersed in 120 mL of ethylene glycol solution. The mixture was stirred overnight until the powder was completely dissolved. The solution was then transferred to a stainless steel high-pressure reactor with a Teflon liner and placed in a 200°C electric heating drying oven for 10 h. After the reaction was complete, the reactor was cooled, and the precipitate in the liner was separated using a magnet. The precipitate was washed several times alternately with deionized water and anhydrous ethanol. The washed precipitate was then vacuum dried at room temperature to obtain Fe3O4 particles.
[0052] Example 1: Characterization of the physicochemical properties of magnetic composite particle materials.
[0053] The magnetic particles P-Fe3O4, F-Fe3O4, and Fe3O4 prepared in the examples and comparative examples were analyzed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM), respectively (preparation methods are as follows). Figure 2 The microstructure of the particles (shown) was observed, and the elemental composition of F-Fe3O4 was analyzed by energy-dispersive X-ray spectroscopy (EDS). Using water as a dispersant, the particle size distribution and Zeta potential of Fe3O4, P-Fe3O4, and F-Fe3O4 were detected using dynamic light scattering and Zeta potential analysis. Nitrogen adsorption-desorption tests were conducted under liquid nitrogen conditions at 77 K using a fully automated specific surface area and porosity analyzer. Parameters such as the specific surface area and pore size distribution of Fe3O4 and P-Fe3O4 were analyzed based on the Brunauer-Emmett-Teller theory (BET).
[0054] SEM images, particle size distributions, and TEM images of the magnetic particles prepared in Example 1 and Comparative Example 1 are shown below. Figure 3 As shown, by comparing the SEM images, it can be found that both Fe3O4 and P-Fe3O4 particles are spherical. Figure 3 (A and B in the text), DLS analysis showed that their particle size distributions were similar (average particle size of approximately 200 nm), while the addition of polyacrylic acid significantly altered the surface morphology of the particles. Figure 3 (B in the text) Using TEM to observe the morphological features at the edge of the particle surface, and observing them at different magnification ratios, can further demonstrate the differences between the two ( Figure 3 (C~H in the middle).
[0055] The effects of the introduction of polyacrylic acid on the surface and pore structure characteristics of particles were compared using a fully automated specific surface area and porosity analyzer. The results showed that the nitrogen adsorption-desorption curves of both exhibited obvious adsorption-desorption hysteresis. Figure 4 The figure A indicates that the pore structure of the material is mainly mesoporous / intergranular pores. Further analysis shows that the specific surface area of P-Fe3O4 is higher than that of Fe3O4, and the average pore size of P-Fe3O4 is significantly smaller. Figure 4 (See B in Table 1). t-Plot results show that P-Fe3O4 has significantly higher micropore area and micropore volume, indicating that the introduction of polyacrylic acid not only increases the overall specific surface area but also enhances the microporous structure. Comparison of the pore size distribution results reveals that P-Fe3O4 exhibits non-zero incremental pore volume in the <4nm range, while Fe3O4 shows almost none, with higher pore volume in the macropore segment (intergranular pores). This indicates that polyacrylic acid can reduce the average pore size of magnetic particles, refine the surface pore structure, and reduce agglomeration, which is beneficial for further surface functionalization modification.
[0056] Table 1. Specific surface area, pore volume, and pore size data determined based on nitrogen adsorption-desorption isotherms. .
[0057] Furthermore, the Zeta potential test results showed that P-Fe3O4 particles exhibited significant negative charge in the aqueous phase. Figure 4 The presence of C in the figure provides further evidence for the reduction in interparticle aggregation and also lays the foundation for the next step of Mg... 2+ The modification provides the basis for implementation.
[0058] Based on the aforementioned differences in pore structure and surface properties, P-Fe3O4 was selected as the core of the magnetic composite particles to support subsequent materials. After gradual modification, F-Fe3O4 particles with a positively charged surface were finally obtained. Figure 3 I and J in Figure 4 The C in the text is missing. SEM and TEM images show that the functionalized composite iron oxide particles F-Fe3O4 have a rough surface morphology and granular protrusions. DLS results show that F-Fe3O4 has a larger particle size than P-Fe3O4 (average particle size approximately 350 nm), indicating the formation of an encapsulation structure on the F-Fe3O4 surface. EDS results indicate that F-Fe3O4 contains carbon, nitrogen, oxygen, magnesium, iron, and copper elements (…). Figure 4 The results (D and E in the figure) provide further evidence for the presence of magnesium ions, copper oxide, and nitrogen-containing organic layers (polydopamine, chitosan).
[0059] Furthermore, according to SEM and TEM images, the appearance and particle size of F-Fe3O4 and P-Fe3O4 prepared in Example 2 are comparable to those in Example 1. Figure 3 The K and L values in Example 2 are different from those in Comparative Example 1, indicating that Example 2 also successfully prepared magnetic particles similar to those in Example 1.
[0060] Experimental Example 2: Characterization of the electromagnetic properties of magnetic composite particle materials.
[0061] The crystal structure and phase composition of P-Fe3O4 and F-Fe3O4 prepared in Example 1 were analyzed by X-ray diffraction (XRD). The magnetic characteristics of the P-Fe3O4 and F-Fe3O4 particles at room temperature were characterized using a vibrating sample magnetometer. Thermogravimetric analysis (TG) was performed to analyze the thermal stability and mass loss behavior of P-Fe3O4 and F-Fe3O4 by heating from room temperature to 800℃ at a rate of 5℃ / min. Fourier transform infrared spectroscopy (FTIR) was used to analyze P-Fe3O4, F-Fe3O4, and the intermediate product P-Fe3O4-Mg. 2 +Chemical functional groups of PDA / CuO. Analysis of P-Fe3O4, F-Fe3O4, and the intermediate P-Fe3O4-Mg by X-ray photoelectron spectroscopy (XPS). 2+ The surface elemental composition and valence state of @PDA / CuO. To investigate the ion release characteristics of F-Fe3O4, 5 mg of F-Fe3O4 particles were dispersed in 1 mL of phosphate-buffered saline (PBS) and transferred to a dialysis bag. The dialysis bag was then immersed in 100 mL of PBS and incubated in a shaker at 37 °C. The dialysate was collected at predetermined time points, and an equal volume of PBS was added. The ion concentrations in the collected liquid were analyzed by inductively coupled plasma mass spectrometry / emission spectroscopy (ICP-MS / OES) to assess the release trends of Fe, Mg, and Cu ions in F-Fe3O4.
[0062] like Figure 5 As shown, the crystal structures of P-Fe3O4 and F-Fe3O4 were analyzed by XRD. The results showed that the XRD patterns of P-Fe3O4 and F-Fe3O4 were highly matched with the standard pattern (JCPDS number 99-0073), and the characteristic peak positions of the two particles were basically consistent. This indicates that the crystal phase of the material remained stable after the multi-step modification process. Figure 5 (A) In addition, compared with P-Fe3O4, the peak intensity and peak width of F-Fe3O4 related to iron tetroxide decreased and increased, accompanied by an increase in background, which may be related to the amorphous scattering caused by the amorphous coating layer of organic components polydopamine and chitosan in the particles.
[0063] The magnetic characteristics of P-Fe3O4 and F-Fe3O4 were evaluated using VSM. Hysteresis loops showed that both exhibited typical superparamagnetic properties at room temperature. The saturation magnetization of P-Fe3O4 was 73.13 emu / g, while the saturation magnetization of F-Fe3O4 decreased due to the presence of various modifiers. Figure 5 (B in the figure). Furthermore, the attached figure also shows that F-Fe3O4, after dispersion, can be attracted, enriched, and separated from the solution by a magnet, demonstrating its good magnetic responsiveness and magnetic recovery capability.
[0064] Thermogravimetric analysis results show that after heat treatment at 800℃, the mass loss of F-Fe3O4 is greater than that of P-Fe3O4 ( Figure 5 The presence of C in the figure indicates the existence of an organic layer.
[0065] FTIR analysis was performed on P-Fe3O4 and P-Fe3O4-Mg during the preparation process. 2+ The chemical functional groups of the products in the three stages of PDA / CuO and F-Fe3O4 are shown in the following results. Figure 5 As shown in D in the figure. For P-Fe3O4, 575 cm⁻¹ 1 The obvious absorption peaks around the left and right can be attributed to Fe in iron(III) oxide. The O stretching vibration indicates the presence of a magnetite core located at 1411 cm⁻¹. 1 and 1546cm 1 The peak can be attributed to the characteristic peak of polyacrylic acid. At 1715 cm⁻¹ 1 The peak at this point can be attributed to the C=O stretching vibration of the free carboxylic acid group, indicating unbound... COO Exposed on the surface, forming a stable negatively charged layer. Through gradual modification, P-Fe3O4-Mg... 2+ @PDA / CuO, F-Fe3O4 at 3440cm 1 The significantly enhanced absorption peak at this point may originate from the O2 of polydopamine and chitosan. H / N The superposition of H stretching vibrations and hydrogen-bonded water; at 2834, 2889, and 2974 cm⁻¹ 1 C can be observed at this location The H stretching vibration, especially the one more pronounced in F-Fe3O4, indicates a gradual increase in organic components; at 1711 1745cm 1 The several weak peaks that appear may originate from C=O. Furthermore, in the P-Fe3O4-Mg... 2+ @PDA / CuO stage, 1500 1650cm 1 A significant change in peak shape was observed, which is related to the aromatic ring structure of polydopamine and overlaps with the vibrations of carboxylates. Notably, this change was observed before the final introduction of chitosan, while the chitosan-related polysaccharide characteristic peaks were significantly enhanced only after the final modification. This indicates that the polydopamine layer existed before chitosan coating and was retained after the successful introduction of chitosan as the outermost layer. (In P-Fe3O4-Mg) 2+ @PDA / CuO and F-Fe3O4 in the low wavenumber region, except for Fe Outside of O, 407 445cm -1 Additional absorption bands were also observed, consistent with metal-oxygen vibrations, providing evidence for the successful loading of copper oxide.
[0066] The surface elemental composition of the magnetic particles was analyzed using XPS, and the results are as follows: Figure 5As shown in E, the full spectrum of F-Fe3O4 can detect elemental signals such as N, Mg, and Cu, indicating the successful introduction of organic and metal components after gradual modification.
[0067] The cumulative release curves of Fe, Mg, and Cu ions from F-Fe3O4 are shown below. Figure 5 As shown in F, the release of Fe and Mg exhibits a relatively stable trend, while the initial release rate of Cu is high, but then gradually stabilizes.
[0068] In summary, the P-Fe3O4 modified with polyacrylic acid exhibits increased specific surface area, reduced average pore size, finer pore structure, and a negatively charged surface. Using P-Fe3O4 as the core of the magnetic composite particles, F-Fe3O4 was prepared through layer-by-layer modification. Characterization results of its chemical functional groups, elemental composition, and valence state demonstrate the successful modification of the P-Fe3O4 particle surface with magnesium ions, polydopamine, copper oxide, and chitosan. The resulting F-Fe3O4 possesses a stable crystal phase structure and good magnetic responsiveness, maintaining a stable release rate in PBS.
[0069] Experimental Example 3: In vitro biocompatibility of magnetic composite particles.
[0070] Human bone marrow mesenchymal stem cells were co-cultured with the magnetic particles prepared in Example 1 under different treatment conditions for 24 hours: the PM group used ordinary proliferation medium (α-MEM + 10% fetal bovine serum + 1% penicillin antibody); the P-Fe3O4 group used ordinary proliferation medium containing 60 μg / mL P-Fe3O4; the F-Fe3O4 group used ordinary proliferation medium containing 60 μg / mL F-Fe3O4; and the F-Fe3O4+SMF group used ordinary proliferation medium containing 60 μg / mL F-Fe3O4. Neodymium iron boron permanent magnets (60 mm in diameter, 20 mm thick) were placed at the bottom of the culture dish, and a static magnetic field of approximately 100 mT was continuously applied at the cellular level to assess the magnetic effect. Cell viability / dead cell staining, cytoskeleton staining, and CCK-8 cell proliferation assays were used to detect the effects of the materials on cell viability, adhesion, and proliferation. Cell scratch assays were used to detect the effects of the materials on cell migration.
[0071] Experimental results are as follows Figure 6 As shown, the live / dead staining results of human bone marrow mesenchymal stem cells in different magnetic particle groups showed that almost all cells in all groups survived (green), indicating a high level of cell viability. At this concentration, the presence of P-Fe3O4 and F-Fe3O4 did not lead to significant apoptosis or damage. Figure 6 (A in the middle).
[0072] Cytoskeleton fluorescence staining showed that cells in all groups were well spread out, exhibiting a typical spindle shape, with clear and evenly distributed actin filaments and intact nuclei. Figure 6 (B) Among them, the cells in the F-Fe3O4 group and the F-Fe3O4+SMF group showed more obvious cell protrusions and extended pseudopodia, indicating that the material has good in vitro biocompatibility and can promote cell adhesion.
[0073] The effect of the material on cell proliferation activity was detected using CCK-8 assay. After 1, 3, 5, and 7 days of culture, the OD values of all groups increased over time, indicating that the cells exhibited significant proliferation activity. Figure 6 (C in the text). At all time points, the P-Fe3O4, F-Fe3O4, and F-Fe3O4+SMF groups were all higher than the PM group ( p <0.001). Meanwhile, the proliferation activity of the F-Fe3O4+SMF group was higher than that of other groups on days 5 and 7 ( p The value <0.001 indicates that the combination of F-Fe3O4 and the static magnetic field can further promote cell proliferation.
[0074] The effects of different treatment conditions on cell migration ability were evaluated using a cell scratch assay. The results showed that the F-Fe3O4+SMF group exhibited the fastest scratch healing at 12 h. p <0.01); at 24h, the scratch healing of the F-Fe3O4+SMF group was still better than that of other groups, followed by the F-Fe3O4 group ( p <0.01)( Figure 6 (D and E in the text).
[0075] In summary, F-Fe3O4 possesses good biocompatibility and bioactivity, which is beneficial to cell extension, adhesion, proliferation and migration. Furthermore, these promoting effects are further enhanced when combined with a static magnetic field, making it suitable for subsequent research on osteogenic capacity.
[0076] Example 4: In vitro osteogenic properties of magnetic composite particle materials.
[0077] Human bone marrow mesenchymal stem cells were co-cultured with the magnetic particles prepared in Example 1 under different treatment conditions and osteogenic induction was performed: the PM group used ordinary proliferation medium; the OM group used osteogenic induction medium (α-MEM + 10% fetal bovine serum + 1% penicillin-dextrose antibody + 10mM β-glycerophosphate sodium + 0.2mM ascorbic acid + 0.1mM dexamethasone); the P-Fe3O4 group used osteogenic induction medium containing 60 μg / mL LP-Fe3O4; the F-Fe3O4 group used osteogenic induction medium containing 60 μg / mL F-Fe3O4; and the F-Fe3O4+SMF group used osteogenic induction medium containing 60 μg / mL F-Fe3O4. The magnetic effects were evaluated under the same static magnetic field conditions. On day 7, alkaline phosphatase (ALP) staining and activity detection, and reverse transcription quantitative polymerase chain reaction (RT-qPCR) were used to detect the effects. ALP and RUNX2 The mRNA expression of F-Fe3O4 was analyzed to assess its effect on early osteogenic differentiation. Mineralized nodules were stained and quantitatively analyzed on day 14, and detected by RT-qPCR. BGLAP and SPP1 The mRNA expression of F-Fe3O4 was analyzed to determine its effect on late osteogenic differentiation.
[0078] On day 7 of osteogenic induction, ALP staining analysis ( Figure 7 The results (A and C in the table) show that the ALP activity in the F-Fe3O4 group and the F-Fe3O4+SMF group was significantly higher than that in other groups. p <0.001); the F-Fe3O4+SMF group was higher than the F-Fe3O4 group ( p <0.001). ALP plays an important role in bone mineralization. It can bind to bone matrix proteins and participate in mineralization regulation by stimulating pyrophosphate hydrolysis. Therefore, it is considered an important biomarker in the early stages of osteoogenesis. The above experimental results indicate that F-Fe3O4 has good early osteogenic potential, and this ability can be further enhanced by the synergistic effect of a static magnetic field.
[0079] Alizarin Red was used to stain mineralized nodules on day 14 of osteogenic induction to determine the mineralization of the extracellular matrix, thereby reflecting the osteogenic activity of cells in the later stage. The results showed a trend consistent with ALP staining results. Figure 7 The mineralized nodules in groups B and D, i.e., the F-Fe3O4 group, were significantly more numerous than those in groups PM, OM, and P-Fe3O4. p <0.001), the mineralization amount of the F-Fe3O4+SMF group is greater than that of the F-Fe3O4 group. p <0.001).
[0080] To further evaluate the ability of magnetic particles and different treatment conditions to promote osteogenic differentiation at the mRNA level, the mRNA expression levels of four osteogenic-related genes were detected by RT-qPCR at corresponding time points during osteogenic induction, including... ALP (7 days) RUNX2 (7 days) BGLAP (14 days) SPP1 (14 days). In the early stages of osteogenic differentiation, ALP and RUNX2 High expression of this substance can promote cell proliferation, differentiation, and bone matrix maturation; in the middle and late stages of differentiation, BGLAP and SPP1 This is mainly related to the mineralization of the bone matrix and the formation of mature bone tissue. The results showed that hBMSCs in the F-Fe3O4 group and the F-Fe3O4+SMF group... RUNX2 and SPP1 The expression level was higher than that of the other three groups. p <0.05), and the F-Fe3O4+SMF group had a relatively higher value; the F-Fe3O4+SMF group ALP and BGLAP The expression level was higher than all other groups. p <0.05)( Figure 7 (E~H in the text). This indicates that F-Fe3O4 can significantly promote osteogenic differentiation of cells, and by combining it with a static magnetic field, it can further upregulate the expression of osteogenic-related genes and increase the levels of biomarkers related to early and late stages of osteogenic differentiation, suggesting that the synergistic treatment of F-Fe3O4 and a static magnetic field has a positive promoting effect on osteogenic differentiation of cells.
[0081] In summary, F-Fe3O4 and static magnetic field can synergistically promote osteogenic differentiation of human bone marrow mesenchymal stem cells in the early (7 days) and middle-late (14 days) stages of osteogenic induction, demonstrating a significant osteogenic advantage.
[0082] Example 5: Study on the in vitro antibacterial properties of magnetic composite particle materials.
[0083] After propagating Escherichia coli, Staphylococcus aureus, and Enterococcus faecalis, they were diluted to 1×10⁻⁶ using the corresponding bacterial culture media. 6 Colony forming units (CFU) / mL were co-cultured with the magnetic particles prepared in Example 1 under different treatment conditions. The control group contained no magnetic particles. The final concentration of magnetic particles in the P-Fe3O4 group, F-Fe3O4 group, and F-Fe3O4+SMF group was 60 μg / mL, and the final bacterial concentration in each group was 5 × 10⁻⁶. 5CFU / mL (a neodymium iron boron permanent magnet was placed at the bottom of the F-Fe3O4+SMF group, and a static magnetic field of the same intensity was continuously applied to evaluate the magnetic effect). Bacterial activity was analyzed by colony counting, and bacterial morphology was observed using scanning electron microscopy.
[0084] The in vitro antibacterial properties of the magnetic composite particles were evaluated by selecting representative Gram-negative bacteria (Escherichia coli), Gram-positive bacteria (Staphylococcus aureus), and common pathogens of periapical periodontitis in the oral cavity (Enterococcus faecalis).
[0085] The plate coating results showed that the number of colonies on the agar plates of the F-Fe3O4 group and the F-Fe3O4+SMF group was less than that of the control group and the P-Fe3O4 group. The F-Fe3O4+SMF group also had fewer colonies than the F-Fe3O4 group. Figure 8 (A) By assessing the survival rate of the three bacteria, it was found that the bacterial activity in the F-Fe3O4 group and the F-Fe3O4+SMF group was significantly reduced compared with the control group and the P-Fe3O4 group. p <0.001); among them, the survival rate of bacteria in the F-Fe3O4+SMF group was consistently lower than that in the F-Fe3O4 group, indicating a decreasing trend in bacterial survival rate. Figure 8 (B~D in the middle).
[0086] SEM observation of bacteria treated under different conditions revealed significant differences in bacterial morphology among different groups. Figure 8 (E). In the control group and the P-Fe3O4 group, Escherichia coli, Staphylococcus aureus, and Enterococcus faecalis all maintained their complete shape and structure, with smooth and plump bacterial surfaces. In contrast, the bacterial surfaces in the F-Fe3O4 group and the F-Fe3O4+SMF group became rough and wrinkled, with obvious morphological changes, suggesting that the bacterial cell membranes were damaged and the bacteria lost their activity.
[0087] In summary, F-Fe3O4 can effectively inhibit the growth of Escherichia coli, Staphylococcus aureus, and Enterococcus faecalis.
[0088] Experimental Example 6: The therapeutic effect of magnetic composite particle material on infectious bone defects in the femur of rats.
[0089] Animal experiments were reviewed and approved by the Biomedical Ethics Committee of Peking University and conducted in accordance with institutional animal experiment guidelines. An infectious bone defect model of the femur was established using 8-week-old male SD rats. Under general anesthesia, a cylindrical defect area of approximately 3 mm in diameter and 3 mm in depth was prepared in the lateral femoral condyle of the rat using a trephine drill, and Staphylococcus aureus suspension was injected into the cavity of the defect to induce infection.
[0090] Prepare a 0.5 w / v% lithium phenyl (2,4,6-trimethylbenzoyl)phosphate initiator solution using PBS and store it protected from light. Add GelMA and the initiator solution to a centrifuge tube, ensuring the GelMA is fully immersed. Heat in a 70°C water bath in the dark for 30 minutes, shaking several times during the process. Centrifuge at 3000 rpm for 2 minutes to remove air bubbles, then immediately sterilize using a 0.22 μm sterile syringe filter to prepare a 20 w / v% GelMA hydrogel solution. Mix the GelMA hydrogel solution with equal volumes of PBS solution without F-Fe3O4 and PBS solution containing 120 μg / mL F-Fe3O4 to obtain 10 w / v% GelMA hydrogel solution and GelMA hydrogel solution containing 60 μg / mL F-Fe3O4, respectively, for subsequent experiments.
[0091] Rats were randomly divided into a control group (no treatment), a GelMA group (injected with GelMA hydrogel), an F-Fe3O4 group (injected with GelMA hydrogel containing F-Fe3O4), and an F-Fe3O4+SMF group (injected with GelMA hydrogel containing F-Fe3O4, and multiple neodymium iron boron permanent magnets were fixed to the cages of these rats; a static magnetic field of the same intensity was continuously applied throughout the treatment to assess the magnetic effect). Muscles and skin were sutured sequentially, and disinfected with iodine. Rats were placed on warming pads until they recovered and regained consciousness before being placed back into their cages. The diet, activity, and wound healing of the SD rats were observed regularly. One week later, the in vivo antibacterial properties of the materials were analyzed: soft tissue around infected bone defects was collected and observed after hematoxylin and eosin (H&E) staining and Giemsa staining; samples were taken from the infected bone defect area for colony counting. The in vivo osteogenic properties of the material were analyzed at 4 and 8 weeks: distal femoral specimens from rats were collected, scanned and reconstructed in three dimensions using micro-computed tomography (micro-CT), and parameters such as bone volume fraction, trabecular bone number, trabecular spacing, and trabecular bone thickness were analyzed; observations were made after H&E staining, Masson staining, and osteocalcin immunofluorescence staining. Furthermore, the in vivo biosafety of the material was analyzed at 1, 4, and 8 weeks: major rat organs were collected and observed after H&E staining.
[0092] (1) In vivo antibacterial properties of magnetic particles.
[0093] The in vivo antibacterial properties of magnetic particles, such as Figure 9 As shown. One week after material implantation, samples were taken from the infected bone defect area for plate smearing and colony counting. The results showed that the bacterial survival rate of the F-Fe3O4 group and the F-Fe3O4+SMF group was better than that of the control group and the GelMA group. p <0.01 indicates that the F-Fe3O4 group and the F-Fe3O4+SMF group have good antibacterial effects in vivo. Figure 9 (A and B in the text).
[0094] Histological staining was performed on the soft tissue surrounding the infected bone defect to further assess inflammation and infection. H&E staining was used to observe the inflammatory response in the soft tissue surrounding the defect, while Giemsa staining was used to observe bacteria in the tissue. H&E staining results showed ( Figure 9 In the C group, both the control group and the GelMA group showed significant and abundant inflammatory cell infiltration, indicating a strong inflammatory response in the tissues. In contrast, the inflammatory cell aggregation trend in the F-Fe3O4 group and the F-Fe3O4+SMF group decreased, while the F-Fe3O4+SMF group showed the least amount of inflammatory cells, suggesting that F-Fe3O4 particles can effectively promote tissue anti-infection, and the combined effect of static magnetic field can reduce the inflammatory response in the tissues. Giemsa staining results ( Figure 9 The D) also showed a consistent trend, with the control group and GelMA group showing significant bacterial aggregation, suggesting local tissue infection, which may lead to persistent infection at the bone defect site and hinder bone regeneration; the F-Fe3O4 group showed a significant decrease in bacteria, while the F-Fe3O4+SMF group showed the least amount of bacterial colonization.
[0095] (2) Osteogenesis properties of magnetic particles in vivo.
[0096] Four and eight weeks after surgery, samples were scanned using micro-CT, and three-dimensional reconstructions were performed on the obtained images. Regions of interest (ROIs) were selected to analyze bone regeneration at the site of infected bone defects. The results are as follows: Figure 10 As shown in the reconstructed images, after 4 weeks, all groups showed repaired bone tissue at the defect site, but the quality of the newly formed bone tissue varied among the groups. Figure 10 (A) In the control group and GelMA group, the new bone formed at the defect site was discontinuous, with irregular, thin, and patchy edges and obvious gaps, failing to cover the entire defect area. The new bone in the F-Fe3O4 group and the F-Fe3O4+SMF group was more continuous, essentially completely covering the defect area. After 8 weeks, the control group and GelMA group formed relatively continuous new bone, covering the defect area, but tissue defects were still visible on the bone surface, and the overall bone volume was low. The new bone volume in the F-Fe3O4 group and the F-Fe3O4+SMF group further increased, and the tissue defects on the bone surface in the F-Fe3O4+SMF group were no longer obvious. Figure 10 (B in the middle).
[0097] Further quantitative analysis of ROI ( Figure 10 As can be seen from the C~F values, the F-Fe3O4+SMF group had the highest bone volume fraction at both 4 and 8 weeks. p <0.05%, followed by the F-Fe3O4 group ( p<0.01), with no difference between the control group and the GelMA group. Trabecular bone number and thickness also showed a similar trend, with the F-Fe3O4 group and the F-Fe3O4+SMF group showing higher values at both weeks 4 and 8 than the other two groups, with the latter reaching its highest value at week 8. p <0.05. The intertrabecular spacing in the control group and GelMA group was significantly larger than that in the F-Fe3O4 group and the F-Fe3O4+SMF group ( p <0.01 indicates poor new bone quality; the trabecular spacing in the F-Fe3O4+SMF group at week 8 was further lower than that in the F-Fe3O4 group ( p <0.05).
[0098] H&E staining and Masson staining were used to study the pathological changes in bone tissue, and the results are as follows: Figure 11 As shown in the figure. H&E staining results showed that the control group and GelMA group had inflammatory cell infiltration, and the bone tissue was disordered and discontinuous, with poor bone formation, indicating limited bone regeneration capacity; the F-Fe3O4 group and F-Fe3O4+SMF group showed richer bone tissue arrangement and a large amount of new bone formation. Figure 11 (A) Collagen fibers are an important component of bone tissue, and Masson staining can be used to observe the growth status of collagen fibers. The results showed that the F-Fe3O4 group and the F-Fe3O4+SMF group produced abundant collagen fibers, which were denser and more structurally complete compared to the control group and the GelMA group. Figure 11 (B in the text). Furthermore, immunofluorescence staining results showed that at 4 and 8 weeks post-surgery, compared to the control group, the F-Fe3O4 group and the F-Fe3O4+SMF group had significantly more osteocalcin-positive (green) areas, indicating new bone formation and active osteogenic activity. Notably, the F-Fe3O4+SMF group exhibited the strongest fluorescence intensity, indicating substantial new bone formation (B in the text). Figure 11 (C in the middle).
[0099] (3) In vivo biosafety of magnetic particles.
[0100] At 1, 4, and 8 weeks, H&E staining of major organs (heart, liver, spleen, lung, and kidney) in rats was performed to assess the inflammatory response of the multifunctional magnetic composite particle material F-Fe3O4 in the host, thus conducting an in vivo biosafety study. Results are as follows: Figure 12 As shown, no obvious pathological changes or tissue morphological abnormalities were observed in any group. Furthermore, no related side effects or acute systemic toxicity were observed. This indicates that the use of this concentration of F-Fe3O4 and the effect of this intensity of static magnetic field have good in vivo biological safety.
[0101] In summary, the combined effect of F-Fe3O4 and static magnetic field can effectively inhibit the growth of bacteria in vivo, alleviate the inflammatory response of tissues, and promote new bone formation. At the same time, F-Fe3O4 has good in vivo biocompatibility.
[0102] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A magnetic composite particle material, characterized in that, Composed of magnetic composite particles, the magnetic composite particles include the following parts from the inside out: The magnetic core comprises magnetite particles modified with polyacrylic acid, wherein magnesium ions are adsorbed on the surface of the magnetite particles. An intermediate transition layer comprising polydopamine wrapped around the surface of the magnetic core, wherein copper oxide is externally loaded onto the polydopamine. An outer wrapping layer, which is composed of chitosan, is wrapped around the outside of the intermediate transition layer.
2. The magnetic composite particle material according to claim 1, characterized in that, The magnetic composite particles have a particle size of 250~550nm.
3. The method for preparing the magnetic composite particle material according to claim 1 or 2, characterized in that, Includes the following steps: Preparation of polyacrylic acid modified magnetite magnetic particles: Soluble iron salts were dissolved in an organic solvent, polyacrylic acid was added, the mixture was transferred to a high-pressure reactor and placed in an electric heating drying oven for high-temperature reaction. After the reaction was completed, the precipitate in the high-pressure reactor was separated by a magnet, washed and then vacuum dried to obtain polyacrylic acid modified magnetite magnetic particles. Preparation of magnetic composite particles: The magnetic particles are dispersed in an aqueous solution of magnesium chloride, and subjected to ultrasonic treatment and mechanical stirring to adsorb magnesium ions on the surface of the magnetic particles; dopamine is added and mixed, then copper oxide is added and mixed to form the intermediate transition layer; chitosan solution is added to the reaction system and reacted in the dark to form the outer coating layer; the reaction product is then washed and vacuum dried to obtain the magnetic composite particles.
4. The method according to claim 3, characterized in that, The specific method for preparing the polyacrylic acid-modified iron oxide magnetic particles is as follows: Polyacrylic acid-modified magnetite particles were synthesized using a one-pot solvothermal method. Samples were weighed at a dosage of 2-5 g of ferric chloride hexahydrate and 10.8 g of sodium acetate powder per 120 mL of solvent and dispersed in an ethylene glycol solution. Then, polyacrylic acid was added at a dosage of 0.025-0.5 g per 120 mL of solvent and stirred overnight until the powder was completely dissolved. The mixture was transferred to a stainless steel high-pressure reactor with a Teflon liner and placed in a 200°C electric heating drying oven for 8-12 hours. After the reaction was complete, the reactor was cooled, and the precipitate in the liner was separated using a magnet. The precipitate was washed several times alternately with deionized water and anhydrous ethanol. The washed precipitate was then vacuum-dried at room temperature to obtain the polyacrylic acid-modified magnetite particles. And / or, the specific method for preparing the magnetic composite particles is as follows: The polyacrylic acid-modified iron oxide magnetic particles were dispersed in a 0.1-0.4 mol / L magnesium chloride aqueous solution, sonicated for 0.25-1 h, and mechanically stirred for 2-8 h. The precipitate was then washed. The precipitate was dispersed in a 10 mM Tris-HCl buffer solution, sonicated for 0.25-1 h, and dopamine was added at a rate of 1-4 mg / mL. The mixture was mechanically stirred for 0.5-2 h. Copper oxide was then added at a rate of 1 / 10-2 / 5 of the mass of the polyacrylic acid-modified iron oxide. The mixture was sonicated for 0.25-1 h and stirred for 1-4 h to allow dopamine to self-polymerize into polydopamine. After the reaction, the precipitate was washed and vacuum dried at room temperature to obtain an intermediate product. A 0.5-2 w / v% chitosan solution was prepared using 1% glacial acetic acid solution. The intermediate product was added at the same volume as the magnesium chloride aqueous solution. After uniform dispersion, a crosslinking agent was added, and the mixture was reacted in the dark for 1-4 h. The product was then washed and vacuum dried at room temperature to obtain the magnetic composite particles.
5. The method according to claim 4, characterized in that, The chitosan solution is prepared as follows: Chitosan powder was dissolved in a pre-prepared 1% glacial acetic acid solution, heated to 50°C, and stirred for 0.5 to 1 hour until the solution was clear and transparent. The pH of the solution was adjusted to 5 to 6 with sodium hydroxide solution, and then filtered to obtain the chitosan solution.
6. The use of the magnetic composite particle material according to claim 1 or 2 in the preparation of medicaments and / or medical devices for treating infectious bone defects.
7. A preparation for treating infected bone defects, characterized in that, Includes the following ingredients: The magnetic composite particle material according to claim 1 or 2; and GelMA hydrogel solution.
8. The formulation according to claim 7, characterized in that, In the formulation, the content of the magnetic composite particle material is 60 μg / mL; And / or, the concentration of the GelMA hydrogel is 10 w / v%. And / or, the formulation is an injectable.
9. A kit for treating infected bone defects, characterized in that, Includes the following parts: The formulation according to claim 7 or 8; and A permanent magnet used to generate a static magnetic field, wherein the permanent magnet is a neodymium iron boron permanent magnet.
10. The kit according to claim 9, characterized in that, The magnetic field strength of the static magnetic field is 100 mT.
Citation Information
Patent Citations
Magnetic system for bone regeneration and preparation method and application thereof
CN121668386A
Magnetothermal asymmetric hydrogel as well as preparation method and bone repair application thereof
CN122302319A
